2022
DOI: 10.3389/fpsyt.2021.806884
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Evidence-Informed and Codesigned Model of Support for Children of Parents With a Mental Illness— “It Takes a Village” Approach

Abstract: Providing support to parents and their children to help address the cycle of intergenerational impacts of mental illness and reduce the negative consequences for children is a key focus of selective prevention approaches in public mental health. However, a key issue for children of parents with a mental illness is the lack of access to early intervention and prevention support when needed. They are not easily identifiable (until presenting with significant mental health issues of their own) and not easily acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
(132 reference statements)
1
9
0
Order By: Relevance
“…Echoing Bronfenbrenner’s Ecological Systems Theory (Bronfenbrenner, 1992 ) that views psychosocial processes to be influenced by multiple levels of the surrounding environment, our study findings highlight that change is needed at multiple systemic levels to promote better relationships between parents and their children, families, HCPs, and wider cultural and political networks. In line with recent calls for a ‘village’ approach of social connectedness for families who experience multiple adversities (Goodyear et al, 2022 ; Reupert et al, 2022 ), a shift in practice approach is indicated, particularly given that Family Focused Practice (FFP) is not widely implemented even within countries that mandate it (Falkov et al, 2016 ; Furlong et al, 2021 ). A strengths-based approach could shift system-wide perceptions of threat, promoting parents’ sense of safety and connection with their children, their parenting roles, and the communities they live within, supporting better access to, and use of, support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echoing Bronfenbrenner’s Ecological Systems Theory (Bronfenbrenner, 1992 ) that views psychosocial processes to be influenced by multiple levels of the surrounding environment, our study findings highlight that change is needed at multiple systemic levels to promote better relationships between parents and their children, families, HCPs, and wider cultural and political networks. In line with recent calls for a ‘village’ approach of social connectedness for families who experience multiple adversities (Goodyear et al, 2022 ; Reupert et al, 2022 ), a shift in practice approach is indicated, particularly given that Family Focused Practice (FFP) is not widely implemented even within countries that mandate it (Falkov et al, 2016 ; Furlong et al, 2021 ). A strengths-based approach could shift system-wide perceptions of threat, promoting parents’ sense of safety and connection with their children, their parenting roles, and the communities they live within, supporting better access to, and use of, support.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, parents’ experiences of navigating relationships with their children and wider systems, and their ideas about parenting support, are not yet fully understood. Consequently, parental needs are often disregarded by services, leaving parents feeling unheard and unsupported (David et al, 2011 ; Goodyear et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Austrian project mentioned at the start of this perspective, titled How to raise a village to raise a child , has a program theory model that the authors argued promotes the capacity of the village to care for children and families; this model outlines resource inputs, systems and individual context considerations and triggers for behavior changes ( 48 ), with a particular focus on translation and implementation ( 49 ). A subsequent article further emphasized the importance of regional context specific solutions and engagement with local and experienced stakeholders to ensure service models are implementation ready ( 50 ). As the authors themselves conceded, their work to date has not yet demonstrated the effectiveness of this approach, especially in terms of child outcomes ( 50 ).…”
Section: Potential Principles Of the Village Approachmentioning
confidence: 99%
“…A subsequent article further emphasized the importance of regional context specific solutions and engagement with local and experienced stakeholders to ensure service models are implementation ready ( 50 ). As the authors themselves conceded, their work to date has not yet demonstrated the effectiveness of this approach, especially in terms of child outcomes ( 50 ). A major issue in the field appears to be that many of these broad community projects have not been rigorously evaluated, especially in regard to how children may benefit.…”
Section: Potential Principles Of the Village Approachmentioning
confidence: 99%
“…The co‐design process and its results are described elsewhere (Goodyear et al . 2022). In summary, six co‐design workshops took place over 6 months using the knowledge from the scoping phase (Fig.…”
Section: Introductionmentioning
confidence: 99%